Role of age stratification for colposcopy referral following initial diagnosis of mild dyskaryosis. Issue 5 (28th January 2008) - Crowther, S; Turner, L; Magee, D; Gibbons, D
Abstract : Introduction: Referral to colposcopy following a single mildly dyskaryotic smear is becoming more widely recommended in the developed world. This has workload and cost implications. Aim: To investigate if stratification of mildly dyskaryotic smears by age group might allow selection of populations that could be followed by repeat cytology initially. Methods: The study set was of all women with a diagnosis of dyskaryosis between July 2004 and June 2005 in an opportunistic screening programme. The dyskaryosis was divided into high grade (moderate and severe) and low grade and ratios of high to low grade were calculated for age groups. The age intervals were under 20 years, and every 5 years from 20 to 54 years. Results: In the study period, a total of 34 180 cervical smears were examined. Of these, 2326 women were diagnosed with dyskaryosis, (1566 (67%) low grade, 760 (33%) high grade) in the given age groups. This gave an overall ratio of high grade to low grade of 1:2. Ratios of high-grade dyskaryosis to low-grade dyskaryosis stayed relatively constant throughout the age intervals from 20 to 54 years of age, Pearson correlation coefficient 0.91, p = 0.0014. Conclusion: The ratios of incidences of grades of dyskaryosis remained constant throughout the age intervals suggesting that selective patterns of referral to colposcopy based on patient's age at diagnosis of mild dyskaryosis are not applicable.